2018
DOI: 10.1007/s11356-018-2390-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and quality assessment of recycled post-consumption poly(ethylene terephthalate) (PET)

Abstract: In the present study, the recycled post-consumption polyethylene terephthalate (PET) flakes were investigated as possible raw materials for the production of food packaging. After heating at 220 °C for 1 h, a steaming stage was conducted as a control test to assess the quality of the product. Different samples were characterized by H-NMR, FT-IR, DSC/TGA analysis, viscosity index (VI), and trace metals analysis. The results showed that the recycled post-consumed PET flakes' properties were generally conform to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…Around 72% of recycled PET is used in fibre applications [21,126]. Mechanically recycled PET suffers from yellowing discoloration but this has been shown to be nontoxic [127]. Recycled PET has a reduction in rheological, mechanical and thermal properties; the reduction significantly increases with the number of recycles (Table 10) [128].…”
Section: Mechanical Recyclingmentioning
confidence: 99%
“…Around 72% of recycled PET is used in fibre applications [21,126]. Mechanically recycled PET suffers from yellowing discoloration but this has been shown to be nontoxic [127]. Recycled PET has a reduction in rheological, mechanical and thermal properties; the reduction significantly increases with the number of recycles (Table 10) [128].…”
Section: Mechanical Recyclingmentioning
confidence: 99%
“…From these four, the recycling product made from PET bottles has been studied the most. The technologies to produce food-grade recycled PET from collected PET bottles have been developed [Welle, 2011] and multiple studies have been conducted on the properties that make recycled PET suitable for application in bottles and trays [Masmoudi et al 2018, Welle 2011. Additionally the relation between the presence of impurities and the properties of recycled PET have been studied [Alsewailem et al 2018, Snell et al 2017, Thoden van Velzen et al 2016, leading to the definition of concentration threshold values for impurities at which the application in PET bottles becomes undesired [Brouwer et al submitted].…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] Masmoudi et al studied whether post-consumer polyethylene terephthalate (PET) flakes could be reused for food packaging. 36 They showed that PET recycling reduces the viscosity and results in the flakes yellowing. And that it does not have any significant effect on their thermal and mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%